Transformation of form in the growth of modern Javanese house in Laweyan Surakarta - Cahyono, Untung Joko; Setioko, Bambang; Murtini, Titin Woro (Journal of Architecture and Urbanism, 2017)
Javanese house tradition grows and develops along time. In the modern era, the development of materials technology, both from the Javanese community and from the European experts, has influenced the way to build a house among the Javanese community. Visible changes are so radical in the use of materials and structural system of the building that they influence the look and shape of the house. The purpose of this research is to study the form transformation in the growth of modern Javanese houses at Kampung Batik Laweyan Surakarta. Laweyan is the traditional Javanese kampung already existing in the Kingdom Pajang long before the birth of Surakarta. Morphological analysis was used to understand deformation of modern Javanese homes developed by the generations of batik entrepreneurs in the 20th century. Indicators of ‘the Javanese origin’ in modern Javanese houses are seen from the consistency of the traditional house configuration, indicated by spatial structure of pendopo, dalem, and gandok. The conclusion is that some Javanese principles still remain in developing modern houses in Laweyan, namely: (1) a house should always be developed creatively to give comfort and protection; and (2) a house should always give benefit and wealth to the owner.